Comparison An Ergonomic Risk Assessment For Repetitive Work Activities On Automotive Workshop Industries Around Parit Raja - Abdol Rahman, Mohd Nasrull; Maniam , Arvind (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Repetitive work, severe exertion and vibration, as well as psychosocial and organizational factors, have all been linked to the formation of Musculoskeletal Disorders (MSDs). Moreover, previous studies had discovered that Musculoskeletal Disorders (MSDs) was mostly linked to the muscles in the neck, back, arms, and legs. The objective of this study to conduct ergonomic risk assessments on 35 automotive maintenance workers around Parit Raja by using Disabilities of the Arm, Shoulder and Hand (DASH) and Assessment of Repetitive Task (ART), Occupational Repetitive Actions (OCRA), and Job Strain Index (JSI) and to correlate Disabilities of the Arm, Shoulder and Hand (DASH) to Repetitive Task (ART), Occupational Repetitive Actions (OCRA), and Job Strain Index (JSI). Statistical Package for Social Sciences (SPSS) was used in this study to analyse the data obtained and to find the Pearson Correlation, p. The average scores for all these score sheets was 14.68 for Disabilities of the Arm, Shoulder and Hand (DASH), 16.66 for Assessment of Repetitive Task (ART), 21.66 for OCRA and 5.31 for Job Strain Index (JSI). The “p” value of Disabilities of the Arm, Shoulder and Hand (DASH) to Assessment of Repetitive Task (ART) was -0.09, Disabilities of the Arm, Shoulder and Hand (DASH) to Occupational Repetitive Actions (OCRA) was -0.26 and Disabilities of the Arm, Shoulder and Hand (DASH) to Job Strain Index (JSI) was -0.15. The results of the comparison were Assessment of Repetitive Task (ART) had the highest Pearson Correlation to the Disabilities of the Arm, Shoulder and Hand (DASH) followed by Job Strain Index (JSI) and Occupational Repetitive Actions (OCRA). In conclusion, ART tool had the highest correlation to the DASH questionnaire followed by JSI and OCRA tool and ergonomic improvement is needed at the automotive workshop in future related to repetitive work activities.